2012
DOI: 10.1029/2011jd016639
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical and NOx production rates, black carbon concentrations and light‐absorbing impurities in snow from field measurements of light penetration and nadir reflectivity of onshore and offshore coastal Alaskan snow

Abstract: [1] Photolytic production rates of NO, NO 2 and OH radicals in snow and the total absorption spectrum due to impurities in snowpack have been calculated for the Ocean-Atmosphere-Sea-Ice-Snowpack (OASIS) campaign during Spring 2009 at Barrow, Alaska. The photolytic production rate and snowpack absorption cross-sections were calculated from measurements of snowpack stratigraphy, light penetration depths (e-folding depths), nadir reflectivity (350-700 nm) and UV broadband atmospheric radiation. Maximum NO x fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
110
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(123 citation statements)
references
References 112 publications
13
110
0
Order By: Relevance
“…Hagler et al (2007) found snow to have a much higher OC to EC ratio (205 : 1) than air (10 : 1), suggesting that snow is additionally influenced by watersoluble gasphase compounds. France et al (2012) demonstrated that black carbon alone could not account for all the absorption seen in the Barrow snowpacks, and an additional absorption by Humic Like Substances (HULIS), part of brown carbon, and other chromophores was necessary to explain variation. Voisin et al (2012) measured HULIS optical properties and reported them to be consistent with aged biomass burning or a possible marine source.…”
Section: Impurities In Snowmentioning
confidence: 99%
“…Hagler et al (2007) found snow to have a much higher OC to EC ratio (205 : 1) than air (10 : 1), suggesting that snow is additionally influenced by watersoluble gasphase compounds. France et al (2012) demonstrated that black carbon alone could not account for all the absorption seen in the Barrow snowpacks, and an additional absorption by Humic Like Substances (HULIS), part of brown carbon, and other chromophores was necessary to explain variation. Voisin et al (2012) measured HULIS optical properties and reported them to be consistent with aged biomass burning or a possible marine source.…”
Section: Impurities In Snowmentioning
confidence: 99%
“…2.2 were not considered. In the case of studies considering multiple light-absorbing impurities in the snow or sea ice, France et al (2012) demonstrated how to separate the effects of different light-absorbing impurities from black carbon for snow on sea ice.…”
Section: Snowpack or Sea Ice Thicknessmentioning
confidence: 99%
“…A fixed value of 0.95 for sea ice and 0.89 for snow were determined, based on the values presented by France et al (2012) and Marks and King (2013). In the two papers, g was held constant and σ scatt and σ + abs varied, based on the methods of Lee Taylor and Madronich (2002).…”
Section: Asymmetry Parametermentioning
confidence: 99%
“…However, light-absorbing impurities, such as black carbon (BC) (e.g. Warren and Wiscombe, 1980;Flanner et al, 2012), dust Painter et al, 2007) and humic-like substances (Hoffer et al, 2006;, impact snow optical properties, especially in the visible range Reay et al, 2012). These impurities are taken into account in TARTES.…”
Section: Impuritiesmentioning
confidence: 99%